(untitled) (Al-Academy, 2016)
My research to study the processes of the creation of shapes and encrypt any encryption in design forms and contents of computer technology as the creative property of definable and renewal, change and transformation process of transformative theme of shape, form and content encryption process in textile designs lets us know the meaning or substance which may be invisible to the encryption in the digital design of fabrics is a recruitment ideas modern and refined through a technique to accomplish the work of a beautiful audiences with novelty and innovation. The search includes four chapters:1Chapter I deal with the problem of research and its current research (form and content encryption with digital designs in women’s contemporary fabrics) it reproduces and innovative design language a new form and production of various new ideas by using the designer’s imagination and encrypt any encryption in the shapes and contents using computer technology and asking the following:Is it possible to obtain women’s contemporary fabric designs effective encryption formats and content of subjects with the possibility of implementation in accordance with digital technology? The objective is to prepare a proposed textile designs contemporary The study identified women’s contemporary fabrics designs implemented in digital technology. Chapter II may combine the theoretical framework and the previous studies and the theoretical framework may include the following: Detective Section i: 1. encrypt form and content in the design.Either section II contained digital design in contemporary fabrics.Either section III contained encrypted designs fabrics according to digital technology.Chapter III procedures for research, research methodology and specified and search tool and search forms. Out in chapter IV of the findings, conclusions and recommendations and design proposals, proposals, and one of the most important result of the research:1. built on encryption in the formal sense as in the direction of expressionist canvas.2. the aesthetic values of textile using modern methods in composition design of form design to technical codes diverse modern digital.4. characteristic designs of textile with utilitarian values achieved a large proportion comes from the aesthetic expression and content forms of cryptographic and expressive and symbolic consistency and harmony of forms and colors in sophisticated style with digital technology.5. the count of shapes and design links and content codes codes and units of semantic interpretation was accurate detail to explain the meanings of the forms and content